The Status of Childhood Lead Poisoning and Prevention in Nevada, USA - Anne M. Rothweiler; Elena E. Cabb; Shawn L. Gerstenberger (The Scientific World Journal)
One of the first steps in addressing the problem of childhood lead poisoning is to identify the possible sources of exposure in specific communities and target high-risk populations with appropriate interventions. Due to several factors, such as lack of funding and lack of blood lead reporting, little information exists regarding the occurrence of childhood lead poisoning and the prevalence of potential exposure sources in the state of Nevada. Following the recent establishment of a Nevada-based Lead Poisoning Program, we compiled the most current information available on Nevadans, and use this knowledge to suggest future research objectives and outreach activities for the state. Accordingly, we identify the characteristics of the vulnerable Nevada populations, explore possible sources of lead exposure unique to Nevada, and summarize the existing data on childhood lead poisoning. Emerging data indicates that Nevada is an area of rapid population growth, characterized by increasing immigration from Latin America, increasing numbers of children from low-income families with no health insurance. Also, childhood lead poisoning may arise from exposure to non-paint sources of lead. After presenting the Nevada statistics, we propose and recommend a set of research and outreach strategies that best suit the needs of Nevada residents.